Analysis of tourism services in the Czech-Polish part of the Euroregion Neisse - Jaroslava Dědková; Otakar Ungerman (Trendy v podnikání, 2020)
The border areas are influenced by the cross-border visitation of tourists, which is usually of a short-term character. These are shopping, exploring natural attractions, commuting to work, visiting friends and relatives, attending cultural and social events, and transit transport. In the course of 2018-2019 a joint research of EF TUL and UE Wroclaw was carried out to determine the quality of tourism services in the Czech - Polish border area. The aim of the research was to find out how respondents perceive and evaluate the quality of services. Almost 1000 respondents on the Czech and Polish side evaluated transport services, accommodation services, sports and recreational services, catering services and the position of information centers. The paper presents the results of this research